Prevalence and localization of the posterior superior alveolar artery in relation to the floor of the maxillary sinus and alveolar crest among sample of Iraqis using computed tomography - Ibrahim, Abdullah A; AlNakib, Lamia H (Journal of Baghdad College of Dentistry, 2017)
Background: Posterior superior alveolar artery (PSAA) is branch of the maxillary artery. It usually supplies the lateral wall of the sinus and overlying membrane. Evaluation and awareness of the anatomy of maxillary sinus before surgery is crucial to avoid surgical complications. The aim of this study is to examine the prevalence, location of the (PSAA) in relation to the floor of the maxillary sinus and alveolar crest using computerized tomography (CT) scans.Materials and Methods: This study included 180 Iraqi subjects (99 males and 81 females) with age more than 16 years old. CT scans for (right and left) Maxillary sinuses were done for each patient. The information obtained was assessed in a coronal multi planar reconstructions images (MPRs) in order to obtain the following parameters: prevalence rate of PSAA, distance from the lower border of the artery to the: alveolar crest, the floor of the sinus and the medial sinus wall.Results: The prevalence of PSAA on CT images was 73.61% among total sample. Distance from the lower border of the artery to the alveolar crest was (18.42± 4.07) mm, and to the sinus floor was (8.99 ±3.86) mm and to the medial sinus wall was (12.68 ± 2.81) mm. Conclusions: CT scan is valuable tool in evaluation and localization of the PSAA before maxillary sinus surgery.